Teacher’s Strategies In Teaching Speaking During Covid-19 Pandemic - Arya Fitri; Hermansyah Hermansyah; Etty Pratiwi; Aswadijaya Aswadijaya (Journal of English Education and Teaching, 2021)
The Covid-19 Pandemic situation made the Government announce  online learning activities.  This policy and it was relationship with teacher strategy at interesting teaching to learn. So that, This research was focused on the strategy that the teacher and used in impelemanting learning during the Covid-19 pandemic. Namely distance learning (PJJ), so that it could runned effectively, optimally, and run well. This research aimed to describe the strategy of teachers in teaching Speking during the Covid-19 Pandemic. This research used a descriptive qualitative approach. The research subject was class VIIB  English teacher, and grade VIIB students. Data collection techniques in this research were observation, interviews, and documentation. The results of the research show that the teacher used an expository strategy that emphasized the teaching and learning process directed to achieve learning objectives.  Analysis of online teacher learning methods with virtual media as a supporting means used two learning methods, first, the assignment method through the google classroom application, the results of the answer sheets were collected directly to the school, and then the second learning method was question and answer through Zoom Meeting and WhatsApp Group. The conclusion obtained from this research was that the teacher strategy in teaching speaking at Junior High School Prabumulih during the Covid-19 Pandemic could be seen from: teaching objectives, teaching approach, and teaching methods.